2002
DOI: 10.1152/ajpregu.00098.2002
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive effects of chronic anti-TGF-β antibody therapy in Dahl S rats

Abstract: This study examined the role of transforming growth factor-␤ (TGF-␤) in the development of hypertension and renal disease in 9-wk-old male Dahl salt-sensitive (Dahl S) rats fed an 8% NaCl diet for 3 wk. The rats received an intraperitoneal injection of a control or an anti-TGF-␤ antibody (anti-TGF-␤ Ab) every other day for 2 wk. Mean arterial pressure was significantly lower in Dahl S rats treated with anti-TGF-␤ Ab (177 Ϯ 3 mmHg, n ϭ 12) than in control rats (190 Ϯ 4 mmHg, n ϭ 17). Anti-TGF-␤ Ab therapy also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 40 publications
4
61
1
Order By: Relevance
“…However, similar findings were reported in older Dahl salt-sensitive hypertensive rats with established glomerular disease: anti-TGF-␤ antibody (1D11) blocked proteinuria and reduced renal TGF-␤ activity but had no effect on glomerulosclerosis or hypertrophy. 67 It was suggested that the reduction in proteinuria without reduced glomerulosclerosis could be due to blockade of the effects of TGF-␤ on glomerular permeability but an inability of the antibody to reverse established fibrosis. 63,67 To address the effect of long-term LSKL therapy on other TGF-␤-mediated functions in diabetes, we studied dermal wound healing in a well-established model of diabetic wound healing in type 2 diabetic mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, similar findings were reported in older Dahl salt-sensitive hypertensive rats with established glomerular disease: anti-TGF-␤ antibody (1D11) blocked proteinuria and reduced renal TGF-␤ activity but had no effect on glomerulosclerosis or hypertrophy. 67 It was suggested that the reduction in proteinuria without reduced glomerulosclerosis could be due to blockade of the effects of TGF-␤ on glomerular permeability but an inability of the antibody to reverse established fibrosis. 63,67 To address the effect of long-term LSKL therapy on other TGF-␤-mediated functions in diabetes, we studied dermal wound healing in a well-established model of diabetic wound healing in type 2 diabetic mice.…”
Section: Discussionmentioning
confidence: 99%
“…67 It was suggested that the reduction in proteinuria without reduced glomerulosclerosis could be due to blockade of the effects of TGF-␤ on glomerular permeability but an inability of the antibody to reverse established fibrosis. 63,67 To address the effect of long-term LSKL therapy on other TGF-␤-mediated functions in diabetes, we studied dermal wound healing in a well-established model of diabetic wound healing in type 2 diabetic mice. 44 TGF-␤ signaling is known to be impaired in diabetic skin wounds, resulting in reduced macrophage chemoattraction, angiogenesis, and extracellular matrix deposition with accelerated reepithelialization.…”
Section: Discussionmentioning
confidence: 99%
“…Dahly et al (40) injected anti-TGF-␤ antibody into salt-loaded Dahl-S rats every day for 2 wk and found a significant decrease in BP, proteinuria, and degree of glomerulosclerosis and renal interstitial fibrosis. Polyamide completely inhibited the increases in proteinuria and albuminuria in salt-loaded Dahl-S rats, along with suppression of TGF-␤1 staining in glomeruli and nephrotubuli.…”
Section: Discussionmentioning
confidence: 99%
“…This can lead to renal scarring and end-stage renal disease in patients with hypertension and diabetes mellitus. On the other hand, chronic anti-TGF-b antibody reduced blood pressure, proteinuria, and the degree of glomerulosclerosis and renal medullary fibrosis in Dahl salt-sensitive rats (Dhaly et al, 2002). In vitro studies revealed that neutralizing TGF-b could inhibit increased synthesis of collagen by cultured mesangial cells in the presence of high glucose.…”
Section: Transforming Growth Factor-b No and Hypertensionmentioning
confidence: 97%